South-South FDI and Development in East Asia - Robert E. Lipsey; Fredrik Sjöholm (Lund University, School of Economics and Management, Department of Economics, 2011)
This paper attempts to measure the size of South-South FDI in developing East Asia and the trends in it, and the characteristics of the investing countries and the investments themselves. It also summarizes the findings of studies in individual countries of the effects of these investments. The studies of individual countries will be used to try to find some consensus on differences between South-South FDI and North-South FDI. Among the comparisons of the two types of FDI we try to summarize are be findings about their industrial composition, their effects on their host countries and their host-country firms' productivity, wages, and employment, and how these differ across industries.
Keywords: F21; F23; O19; 330; FDI; East Asia; South-South; Economic development; Multinational firms